Actinocyclus aquae-dulcis sp. nov. (Coscinodiscophyceae, Coscinodiscales, Hemidiscaeae), a new centric diatom from Lake Akan and northern coasts of Japan - Chiba, Takashi; Osada, Ryosuke; Tuji, Akihiro; Idei, Masahiko (Phytotaxa, 2025)
Morphological classification and molecular analysis were performed on a diatom species of the genus Actinocyclus collected from freshwater Lake Akan, eastern Hokkaido, Japan. This species is characterized by possessingmultiple horseshoe-shaped rimoportulae, a feature not found in other Actinocyclus species. This species was reported in a previous study, in which it was given the tentative species name and in this paper, we formally define the taxon as a new species as Actinocyclus aquae-dulcis. We also report another occurrence of A. aquae-dulcis sp. nov. from the Yoneshiro River mouth area, Akita, Japan.